2016
DOI: 10.1080/14017431.2016.1196826
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac replacement therapies: outcomes and costs for heart transplantation versus circulatory assist

Abstract: The LVADHTx and HTx groups showed excellent one- and five-year survival. The combined group of DWL and HTx patients had similar survival to the combined groups of MCS, but use of LVAD pre-transplant quadrupled the cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
1
19
2
Order By: Relevance
“…In-hospital mortality was found to be significantly higher for HTx waiting list patients compared to BTT LVAD patients (42.3% vs. 4.3%, P=0.002). Although almost all of the included studies, similarly to our overall results, did not find statistically significant differences in 1-year mortality between DT LVAD and HTx patients, Mishra et al found that DT LVAD patients had inferior short term survival comparing to HTx (17). However, this study was limited by its small size.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In-hospital mortality was found to be significantly higher for HTx waiting list patients compared to BTT LVAD patients (42.3% vs. 4.3%, P=0.002). Although almost all of the included studies, similarly to our overall results, did not find statistically significant differences in 1-year mortality between DT LVAD and HTx patients, Mishra et al found that DT LVAD patients had inferior short term survival comparing to HTx (17). However, this study was limited by its small size.…”
Section: Discussioncontrasting
confidence: 40%
“…After removal of duplicates, we assess for eligibility 2,849 studies. We excluded 2,809 studies based on their title and abstract and 40 articles were retrieved for full-text review, before resulting in the eight eligible studies (11)(12)(13)(14)(15)(16)(17)(18). The detailed flow diagram is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To improve organ utility, there has been the implementation of expanded criteria, and a call for the development of a cardiac allocation score, 5,6 as well as the implementation of the October 2018 UNOS heart transplantation policy changes 7 . With improved technology, we have seen that many patients today have been successfully bridged to OHTx with durable ventricular assist devices with 1 year survival of 96% and 5 year survival of 83% 8 . During the study period, 30% of our OHTx had an LVAD in place.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is a huge financial burden, accounting for more than $30 billion in the US alone in 2007 3 . Mishra et al 8 found that total the total hospital costs at 1 year in patients that died on the waiting list was $102 101 ± 202 604, $151 685 ± 86 892 for OHTx, $427 337 ± 365 154 for LVAD, and $600 897 ± 198 109 for OHTx following LVAD. From 2005 to 2009, the mean cost per patient increased for both LVAD and OHTx, 17%, and 40%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation